The level of acceptance towards TikTok changing the beauty standard in Malaysia / Ahmad Luqman Mohd Shamsul Amri, Nurul 'Atiqah Mohammad Bakhtiar and Muhammad Syahmi Fitri Abdul Wahid - Mohd Shamsul Amri, Ahmad Luqman; Mohammad Bakhtiar, Nurul 'Atiqah; Abdul Wahid, Muhammad Syahmi Fitri (Faculty of Communication & Media Studies, 2023)
Social media platforms especially TikTok is well known and is one of the main platforms that have huge number of users across the world. It has become a habit or essential to the the users to at least spend a couple hours using TikTok daily. This study is done in order to find the level of acceptance towards TikTok changing the beauty standard in Malaysia. TikTok are chosen because of the amount of the users are big and often time being related to beauty standard issues in Malaysia. Technology has the potential to lead us to feel self-conscious, but it also provides an alluring and partially satisfactory alternative, with editing apps allowing users to quickly and easily remove flaws and imperfections. This study used cultivation theory as foundations theories for model development. The minimum sample size was determined through Rao soft Sample Size Calculator software. The study employs a quantitative approach via the Google Form platform, with 392 respondents from various backgrounds partaking. The findings indicate that most respondents are aware that TikTok is altering the standards of beauty (M=3.00), and with the information provided, the majority of respondents are also in agreement with how TikTok affects their own sense of self-esteem (M=2.63).